Strategi Kepala Sekolah dalam Meningkatkan Mutu Pendidikan di SD Negeri 21 Bengkulu Tengah - Marea Ahmad (Jurnal Indonesia Pendidikan Profesi Guru, 2024)
The success of an educational institution is highly dependent on the leadership of the principal, the success of the school is the success of the principal. The purpose of this study was to determine the principal's strategy for improving the quality of education at SDN 21 Bengkulu Tengah. This research is descriptive. This research was conducted in 2021. The location of this research is SDN 21 Bengkulu Tengah. Data collection using interviews, observation, and documentation. Data analysis In this qualitative research the author uses the Miles and Huberman model analysis. The results showed that the principal's strategy in improving the quality of education at SDN 21 Bengkulu Tengah has been implemented quite a lot from the existing theories of developing the quality of education. The conclusion of the study resulted the finding that the principal as an administrator, especially in financial management, to achieve an increase in teacher competence must be supported by an adequate cost allocation factor, therefore how much the school can allocate a budget to increase teacher competence will certainly affect the level of competence of its teachers.